2012
DOI: 10.1093/beheco/ars206
|View full text |Cite
|
Sign up to set email alerts
|

Green symphonies: a call for studies on acoustic communication in plants

Abstract: Sound and its use in communication have significantly contributed to shaping the ecology, evolution, behavior, and ultimately the success of many animal species. Yet, the ability to use sound is not a prerogative of animals. Plants may also use sound, but we have been unable to effectively research what the ecological and evolutionary implications might be in a plant’s life. Why should plants emit and receive sound and is there information contained in those sounds? I hypothesize that it would be particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 96 publications
0
62
0
10
Order By: Relevance
“…Foliage planted along freeways to reduce noise pollution often grows differently than foliage planter in a quiet environment [3], [4]. It would be advantageous for plants to learn about the surrounding environment using sound, as acoustic signals propagate rapidly and detection of sound may have adaptive value in plants [5]. Plants are complex multicellular organisms considered as sensitive as humans for initial assaying of effects and testing new therapies [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…Foliage planted along freeways to reduce noise pollution often grows differently than foliage planter in a quiet environment [3], [4]. It would be advantageous for plants to learn about the surrounding environment using sound, as acoustic signals propagate rapidly and detection of sound may have adaptive value in plants [5]. Plants are complex multicellular organisms considered as sensitive as humans for initial assaying of effects and testing new therapies [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…The result revealed that in both the varieties altering magnetic field treated seeds showed increase root and sugar yield compared to control. Galland and Pazur (2005) reported that a magnetic field of magnitude one or two orders above geomagnetic field strength (35 to 70 ìT) could affect plant growth and metabolism. Samy (1998) had found out early flowering and yield increase of cabbage as a result of the treatment with a magnetic field at 8-hours exposition.…”
Section: Magnetic Field Energymentioning
confidence: 99%
“…1984). It would be advantageous for plants to learn about the surrounding environment using sound, as acoustic signals propagate rapidly and detection of sound may have adaptive value in plants (Gagliano, 2012). Plants are complex multicellular organisms considered as sensitive as humans for initial assaying of effects and testing new therapies (Benford, 2002).…”
Section: Sound Energymentioning
confidence: 99%
“…Also contributory is the work of Gagliano who asserts that plants not only collect environmental information to act on but can also be taught, are able to remember and can transmit acoustic messages regarding environmental conditions (Gagliano, 2013a(Gagliano, , 2013bGagliano et al, 2012aGagliano et al, , 2012bGagliano et al, , 2012cGagliano et al, 2014;Gagliano & Renton, 2013). For example, a recent piece of work examines whether Mimosa pudica can become habituated to repetitive stimuli (Gagliano et al, 2014).…”
Section: Uniting the Kingdomsmentioning
confidence: 99%